Role of Talent Management and Culture in Performance at Perum Perhutani - Hermanto, Hermanto; Hudzafidah, Hudzafidah; Marifah, Muliatul (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Enhancing the effectiveness of employees within an organization to achieve both quality and quantity in goal attainment is a primary objective. This pursuit considers a thorough evaluation of assessments and respects the organizational cultural values. This research aims to explore the impact of Talent Management, Organizational Culture, and Competence as moderating factors on employee performance within Perum Perhutani City